2018
DOI: 10.3389/fpls.2018.00608
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) Gene Family in Betula luminifera

Abstract: As a major family of plant-specific transcription factors, SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) genes play vital regulatory roles in plant growth, development and stress responses. In this study, 18 SPL genes were identified and cloned from Betula luminifera. Two zinc finger-like structures and a nuclear location signal (NLS) segments were existed in the SBP domains of all BlSPLs. Phylogenetic analysis showed that these genes were clustered into nine groups (group I-IX). The intron/exon structure and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 65 publications
6
36
0
Order By: Relevance
“…The SPL3 protein belongs to SBP family and contains the conserved SBP domain. It is an important plant-specific transcription factor regulating plant growth and development, and the two zinc finger structures are located in the core region of the SBP domain [32]. According to the gene variants, there are four amino acid substitutions, one of which is a serine to alanine change located in the second zinc-finger structure of SBP domain [10].…”
Section: Discussionmentioning
confidence: 99%
“…The SPL3 protein belongs to SBP family and contains the conserved SBP domain. It is an important plant-specific transcription factor regulating plant growth and development, and the two zinc finger structures are located in the core region of the SBP domain [32]. According to the gene variants, there are four amino acid substitutions, one of which is a serine to alanine change located in the second zinc-finger structure of SBP domain [10].…”
Section: Discussionmentioning
confidence: 99%
“…SBP genes were also found in green plants and referred to as the SQUAMOSA PROMOTER BINDING-LIKE (SPL) genes [18]. In recent decades, the SBP gene families were characterized in model plants, woods, crops, and fruits, such as Arabidopsis thaliana [19], barley [20], green algae [21], moss [22], tomato [23], salvia [24], rice [25], birch [26], light birch [27], cotton [28], grape [29], apple [30], corn [31], and so on. All SPL genes contain a highly conserved DNA binding domain, which was called the SBP-box domain, and it consists of approximately 80 amino acid residues including two zinc finger structures and one nuclear localization signal [32].…”
Section: Introductionmentioning
confidence: 99%
“…SOC1 also negatively regulates SPL3, SPL4, and SPL5 to form a feedback loop [13]. At present, the functions of SPL genes in more and more species has been unearthed: Grape VpSBP11 can regulate floral transition and leaf development [36]; BlSPLs in Betula luminifera interact with DELLA protein to participate gibberellin regulation [27]. It is reported that, except flowering, SPL genes are vital in also other physiological processes in plants, such as adventitious root development [13,37], fertility [38], fruit growth and quality [39], floral organ and shoot development [40,41], plant hormone response [42], morphological differentiation [43], and stresses response [44].…”
Section: Introductionmentioning
confidence: 99%
“…The SPL3 protein belongs to SBP family and contains the conserved SBP domain. It was an important plant-specific transcription factor regulating plant growth and development, and the two zinc finger structures are located in the core region of the SBP domain [24]. According to the gene variants, there are four amino acid substitutions, one of which is a serine to alanine change located in the second zinc-finger structure of SBP domain [8].…”
Section: Discussionmentioning
confidence: 99%